Adding a modified Lemaire procedure to ACLR in knees with severe rotational knee instability does not compromise isokinetic muscle recovery at the time of return-to-play - Leopold Joseph; Guillaume Demey; Thomas Chamu; Axel Schmidt; Alexandre Germain; Floris van Rooij; Mo Saffarini; David Dejour (Journal of Experimental Orthopaedics, 2020)
Abstract Purpose To determine whether isokinetic muscle recovery following ACLR using a hamstring tendon (HT) would be equivalent (non-inferior) in knees that had high-grade pivot-shift and adjuvant modified Lemaire procedure versus knees that had minimal pivot-shift and no adjuvant modified Lemaire procedure. Methods We evaluated 96 consecutive patients that underwent primary ACLR. Nine were excluded because of contralateral knee injury, and of the remaining 87, ACLR was performed stand-alone in 52 (Reference group), and with a Lemaire procedure in 35 (Lemaire group) who had high-grade pivot-shift, age < 18, or genu recurvatum > 20°. At 6 months, isokinetic tests were performed at 240°/s and 90°/s to calculate strength deficits of hamstrings (H) and quadriceps (Q). At 8 months, patients were evaluated using IKDC, Lysholm, and Tegner scores. Results Compared to the Reference group, the Lemaire group were younger (23.0 ± 2.5 vs 34.2 ± 10.5, p = 0.021) with a greater proportion of males (80% vs 56%, p < 0.001). The Lemaire group had no complications, but the Reference group had one graft failure and one cyclops syndrome. Strength deficits at 240°/s and at 90°/s were similar in both groups, but mixed H/Q ratios were lower for the Lemaire group (1.02 ± 0.19 vs 1.14 ± 0.24, p = 0.011). IKDC and Lysholm scores were similar in both groups, but Tegner scores were higher in the Lemaire group (median, 6.5 vs 6.0, p = 0.024). Conclusions ACLR with a modified Lemaire procedure for knees with rotational instability grants equivalent isokinetic muscle recovery as stand-alone ACLR in knees with no rotational instability. For ACL-deficient knees with high-grade pivot-shift, a Lemaire procedure restores rotational stability without compromising isokinetic muscle recovery. Study design Level III, comparative study.